The Impact of Adventure-Based Learning in Outdoor Education on Student SEL and Wellness - Muhamad Yuliyanto; Imam Santosa Ciptaning Wahyu Winarno (Universitas Negeri Semarang, 2026)
This research is motivated by the monotony of conventional Physical Education learning at the junior high school level which triggers student boredom, decreases learning motivation, and has an impact on decreasing physical fitness and weakening students' social-emotional skills. This study aims to determine the effect of implementing the Adventure-Based Learning (ABL) model in outdoor education on improving students' Social-Emotional Learning (SEL) and physical fitness. Using a quantitative approach with a quasi-experimental method and a non-equivalent control group design, this study involved an experimental group (class VIII-C, n=30) who were given 8 sessions of ABL model treatment, and a control group (class VIII-F, n=30) with conventional learning. Data were collected through SEL questionnaires and Multistage Fitness Test (MFT), then analyzed using the Independent Sample T-Test in SPSS. The results of the hypothesis test showed a significance value of 0.000 (p <0.05) for both variables. The average SEL score of the experimental group increased by 16.75 and physical fitness (VO2 Max) increased by 6.40. In conclusion, the ABL model has a significant and effective influence in achieving the dual objectives of physical education, both in the psychological (mental) and biological (physical) aspects of students simultaneously.